Al-Tasawuf wa Azmah al-MustadÄmah: MuqÄrabah Mutaâ€™addidah al-Takhaá¹£á¹£uá¹£Ät Li IdÄrah al-NufÄyÄt fÄ« Indonesia Mustawá¸¥Ät min MafhÅ«m al-KhilÄfah fÄ« RasÄil al-NÅ«r: Tasawwuf and Sustainability Crisis: A Multidisciplinary Approach to Waste Management in Indonesia Inspired by the Concept of Caliphate in the Risale-i Nur - Mudin, Moh. Isom; Huringiin, Nabila; Ouannes, Mohamed Hedi; TÃ¼rkoÄŸlu, TuÄŸba (University of Darussalam Gontor, Indonesia, 2024)
This research explores the relationship between the concept of Khilafah in the Risale-i Nur and the